MANAJEMEN KURIKULUM DALAM PERSPEKTIF AL-QURAN - Rohimat, Sonny; Muiz, Rizqi Nurlaili; Lugowi, Rifyal Ahmad; Subekhan, Moch. (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2025)
One of the important things that must be considered in the development or integration of Islamic values in Islamic education management is the curriculum. The purpose of writing this paper is to analyze the verses of the Qur'an related to curriculum management in Islamic educational institutions. Through the literature study method, this study analyzes Surah Ali Imran verses 190-191, which can be used as a guideline in developing a curriculum integrated with Islamic values. The scope of the curriculum analyzed in this study is related to the objectives and content of the curriculum. There are three main characteristics that must be integrated in relation to the objectives of the Islamic education curriculum, namely the character of dhikr (spirituality), the character of fikr (critical thinking), and amal pious (beneficial actions). The development of curriculum content based on the three characters that are the objectives of the curriculum includes Islamic knowledge, general knowledge, community service projects, and physical development. The results of the analysis show that the objective of Islamic education curriculum management is to form individuals who are not only knowledgeable but also have good morals and are able to make positive contributions to society.